TRUNK MOBILITY AFTER MINIMALLY INVASIVE ONE-LEVEL LUMBAR INSTRUMENTATION - SIMÕES,MARCELO SIMONI (2016)
ABSTRACT Objective: To evaluate the impact of a minimally invasive lumbar one-level fixation on trunk mobility and quality of life compared with the preoperative condition in 26 consecutive patients. Methods: The following data were collected preoperatively and postoperatively for the statistical analysis: maximal trunk extension and flexion angles, Visual Analog Scale of pain and Oswestry Disability Index scores. Results: There was improvement in all variables. Statistical significance was observed in trunk extension, pain, and Oswestry Disability Index. Although mobility in trunk flexion was higher in average values after surgery, this difference was not statistically demonstrated. Conclusion: Minimally invasive one-level lumbar fixation does not cause reduction of trunk flexibility in comparison to the mobility before surgery.